Some key concepts of Critical Rhetoric - McKerrow, Raymie (2023)
This interview highlights the academic career of the Professor Emeritus Raymie McKerrow and some key concepts of Critical Rhetoric (CR) since its proposition until his most recent publications. The methodological steps of this interview were as follows: a first contact with the teacher to obtain his acceptance to carry out the interview and the constant emails exchange in order to elaborate questions and answers. In this dialogue, there was a chance to discuss the multidisciplinary outline of that rhetoric perspective and the importance of Foucault’s theory of power for the formulation of the concepts of critique of freedom or domination, and the dialectic of control. Furthermore, it is possible to understand the appropriation done by CR to generate changes in the social relationships built in society. Finally, it is pointed up the significance of the author’s work since he established the basis of a new rhetorical perspective.